State Estimation for Electrolytic Capacitor with Parameter Fitting - Wang Lei; Xu Chunmei; Du Huiqing; Meng Linghui (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Metro supply system composed of PWM rectifier, i.e. supply system with bi-directional power flow, contributes much to improve supply quality. However, the electrolytic capacitors, working as DC-side supporting capacitor, are relatively weakest in the whole system, so that state estimation for electrolytic capacitor should be taken into consideration. In view of the difficulty in application of conventional capacitor estimation approach with voltage and current ripples into PWM rectifier, this paper proposes a novel approach, which first searches into capacitor’s aging mechanism, presents approximate relation between capacitance and equivalent serial resistance of electrolytic capacitor through mathematical fitting, and then derives the discrete iterative equations of  capacitance and equivalent serial resistance from the analytical model of PWM rectifier. Finally, capacitor state estimation is combined with Miner criterion, which implies digital accumulated damage principle. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3049